Нова методологія досягнення адекватності анестезії та периопераційного антистресорного захисту - Бойцова, Олеся Миколаївна; Boitsova, O. M. (Запорізький державний медичний університет, 2019)
В диссертации приведено теоретическое обобщение и обосновано новое решение научно-практической задачи повышения эффективности лечения пациентов с острой абдоминальной хирургической патологией, путем персонифицированного придания периоперационному анестезиологическому обеспечению енергопротективной способности, основываясь на определении потребности в потреблении кислорода и енергоструктурного статуса больных. Работа выполнена по результатам периоперационного аудита енергоструктурного статуса, его резервов, свойств, эффективности ауторегуляции 317 больных в возрасте от 18 до 86 лет с острой брюшнополостной патологией, которым были выполнены оперативные вмешательства в экстренном и срочном порядке в условиях седоаналгезии, ингаляционной и внутривенной анестезии. Путем определения уровня маркера повреждения нейронов головного мозга нейронспецифической енолазы, обнаружили при всех применяемых стандартных методах анестезиологического обеспечения повреждения клеток головного мозга. Дополнение стандартов периоперационного анестезиологического обеспечения энергопротективными технологиями снижает риск возникновения микроповреждений головного мозга и существенно повышает энергопротективную способность анестезии, что улучшает результаты лечения и тем самым сокращает время пребывания больного в стационаре. The dissertation presents a theoretical generalization and substantiates a new solution to the scientific and practical problem of improving the efficiency of patients’ with acute abdominal surgical pathology treatment by giving personalized energyprotective capacity to perioperative anesthetic management, based on the definition of oxygen consumption needs and the energy-structural status of patients. The study included 317 patients aged 18 to 86 years with acute abdominal pathology, who underwent emergency and urgent surgical interventions. Depending on the type of anesthesia patients were divided into three main groups: with sedoanalgesia, inhalation anesthesia and intravenous anesthesia. According to the initial oxygen consumption level all patients were divided into such groups: with the euenergystructural status(148-192 mlО2/min˟m2), with the dysfunction (147-105 or 193-244 mlО2/min˟m2), with the damage (85-104 or 235-381 mlО2/min˟m2), and with the insufficiency (less than 85 mlО2/min˟m2) of the energy-structural status. Patients in each group were randomly divided into the treatment group and the control group that were representative. Patients of the control group underwent standard anesthesia and intensive care. Patients of the treatment group underwent standard perioperative treatment with the use of energy-protective techniques: energybiotic homeostasis, energyprotection, energyresustitation and status-correction. At twelve perioperative stages a deep picture of the oxygen regime, a danger of energy-structural deficit or energy-structural safety, the dynamics of energy-structural status, its properties, reserves, effectiveness of autoregulation and markers of early signs of neuronal and neuroglial damage (neuron-specific enolase – NSE, protein S100) were studied.
New methodology for achieving adequacy of anesthesia and perioperative antistress protection
Keywords: безпека хворого; інтраопераційний моніторинг; місцева анестезія; седація; інгаляційна анестезія; внутрішньовенна анестезія; метаболізм; споживання кисню; кальцій-зв'язуючий білок S100; фосфопіруват-гідратаза (енолаза); Patient Safety; Intraoperative Monitoring; Anesthesia Local; Conscious Sedation; Anesthesia Inhalation; Anesthesia Intravenous; Metabolism; Oxygen Consumption; S 100 Calcium Binding Protein beta Subunit; Phosphopyruvate Hydratase